Neck Findings of Hanging and Strangulation Cases That Underwent Autopsy in Adana - Hilal, Ahmet; Çekin, Necmi; Gülmen, Mete Korkut; Yıldırım, Kemal Çağdaş (The Bulletin of Legal Medicine, 2011)
Deaths due to the mechanical forces applied to the neck are frequently encountered in forensic medicine practice. Among these, hanging accounts for the majority of the forensic cases. Strangulation cases are also seen though not common. The present study was performed to determine the prevalence of neck findings in the hanging and strangulation cases that are frequently encountered by the forensic medicine specialists, as well as to discuss the results in the light of the literature. The records of the autopsies performed at Forensic Medicine Institution Adana Group Authority Morgue Specialty Office between the years 2008 and 2009 were retrospectively reviewed. One hundred and seventy cases (6.2%) that were assessed to have died due to a neck pressure (hanging or strangulation) were included in the study out of2726 cases. Of the cases, 159 have died of hanging and 11 have died of strangulation. It was determined that 104 (61.2%) of the cases were male and 66 were female, hanging accounted for 93.5% and strangulation accounted for 6.5%, all of the hangings were suicidal, whereas the strangulations were murder. Ages of the cases ranged between 4 and 86 years; the majority of the cases (n=37, 21.7%) were between 21 and 30 years of age, whereas 32 cases were between 11 and 20 years of age. It was determined that there were two girls between the ages 0 and 10 years and have died of strangulation. It was observed that 121 of the hanging cases were typical (the node was behind the neck), whereas 38 were atypical. Thyroid cartilage fracture was determined in 43 (25.3%) cases died of hanging and strangulation, whereas hyoid bone fracture was determined in 25(14.7%) cases and both thyroid cartilage fracture and hyoid bone fracture were determined in 11(6.5%) cases. Fracture or dislocation in cervical vertebra was observed in 7 cases. Totally 86 (50.6%) cases had thyroid cartilage, hyoid bone and cervical vertebra findings. Key words: Hanging, strangulation, neck pressure, autopsy, forensic medicine.